EFEKTIVITAS METODE PEMBELAJARAN SNOWBALL THROWING PADA MATA PELAJARAN AL-QUR’AN HADIST UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS XI DI MAN 1 JOMBANG - Hilyah Ashoumi; Ning Fitriani, Irsa; Dzikrul Hakim Al-Ghozali, M. (Universitas Nahdlatul Ulama Sunan Giri, 2019)
The purpose of this research is to determine the effectiveness of Al-Qur’an Hadist learning in increasing interest by using the learning method of Snowball Throwing class XI IPS MAN 1 Jombang on mujahadatun-nafs, ukhuwah, and husnuz-zann material. This research method uses an experimental method by conducting pre-test-post test. There are two classes, namely class XI IPS 5 as an experimental class using snowball throwing learning model and class XI IPS 4 as a control class using conventional methods. From the test data, it can be seen that the average value of the experimental class and the control class with the number of students 36 per class has increased. The average pre-test value of the control class was 62 and the average post-test score was 91 while the average pre-test score of the experimental class was 72 and the average post-test score was 86. Based on the results of the SPSS analysis of 16.0, a sig value was obtained. (2-tailed) of the experimental class and the control class post-test is 0,02, which means less than 0.05. So it can be concluded that H1 is accepted then there is significant difference between the experimental class post-test and the control class post-test.